(untitled) (Conferencea, 2023)
In research conducted by psychology, the problem of choice and its role in personality formation is one of the main problems of human life. The existing system of education in secondary school places the graduate of the basic stage before the need to make a serious choice in determining his position in relation to the educational profile of grades 9-11. Based on several age characteristics, high school students have serious difficulties in solving this problem and, of course, need specially organized support.